Diagnostic performance of cardiac magnetic resonance segmental myocardial strain for detecting microvascular obstruction and late gadolinium enhancement in patients presenting after a ST-elevation myocardial infarction - Gräni, Christoph; Stark, Anselm W.; Fischer, Kady; Fürholz, Monika; Wahl, Andreas; Erne, Sophie A.; Huber, Adrian T.; Guensch, Dominik P.; Vollenbroich, René; Ruberti, Andrea; Dobner, Stephan; Heg, Dik; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Microvascular obstruction (MVO) and Late Gadolinium Enhancement (LGE) assessed in cardiac magnetic resonance (CMR) are associated with adverse outcome in patients with ST-elevation myocardial infarction (STEMI). Our aim was to analyze the diagnostic performance of segmental strain for the detection of MVO and LGE. Methods Patients with anterior STEMI, who underwent additional CMR were enrolled in this sub-study of the CARE-AMI trial. Using CMR feature tracking (FT) segmental circumferential peak strain (SCS) was measured and the diagnostic performance of SCS to discriminate MVO and LGE was assessed in a derivation and validation cohort. Results Forty-eight STEMI patients (62 ± 12 years old), 39 (81%) males, who underwent CMR (i.e., mean 3.0 ± 1.5 days) after primary percutaneous coronary intervention (PCI) were included. All patients presented with LGE and in 40 (83%) patients, MVO was additionally present. Segments in all patients were visually classified and 146 (19%) segments showed MVO (i.e., LGE+/MVO+), 308 (40%) segments showed LGE and no MVO (i.e., LGE+/MVO–), and 314 (41%) segments showed no LGE (i.e., LGE–). Diagnostic performance of SCS for detecting MVO segments (i.e., LGE+/MVO+ vs. LGE+/MVO–, and LGE–) showed an AUC = 0.764 and SCS cut-off value was –11.2%, resulting in a sensitivity of 78% and a specificity of 67% with a positive predictive value (PPV) of 30% and a negative predictive value (NPV) of 94% when tested in the validation group. For LGE segments (i.e., LGE+/MVO+ and LGE+/MVO– vs. LGE–) AUC = 0.848 and SCS with a cut-off value of –13.8% yielded to a sensitivity of 76%, specificity of 74%, PPV of 81%, and NPV of 70%. Conclusion Segmental strain in STEMI patients was associated with good diagnostic performance for detection of MVO+ segments and very good diagnostic performance of LGE+ segments. Segmental strain may be useful as a potential contrast-free surrogate marker to improve early risk stratification in patients after primary PCI.